Nanoparticle effects on the electrical and thermal performance of the transformer mineral oil - Kadim, Emran Jawad; Ahmad Noorden, Zulkarnain; Adzis, Zuraimy; Azis, Norhafiz (IEEE, 2023)
Mineral oil has been used as a dielectric medium in transformers for more than a century. The enhancement of its performance using nanoparticles (NPs) has been investigated by many researchers in the last two decades. Based on that, in this article, NPs were introduced to improve the electrical and thermal properties of mineral oil. This article presents a model based on the use of COMSOL Multiphysics to evaluate the streamer cur- rent density, net space charge, and oil temperature. In this model, the electrostatics module, the stabilized convection–diffusion equation module, and the coeffi- cient form of partial differential equations (PDEs) were combined. The results include the effects of different parameters of NPs: the size, time constant, and mobility of NPs. These results reflected the importance of the NPs’ time constant and how the NP’s mobility can influence the electrical and thermal characteristics of the oil. However, the results revealed that the volume of NPs had negligible effects on oil performance.